Networking narrative: a rhetorical analysis of the Lizzie Bennet Diaries - Page, Lydia, author; Langstraat, Lisa, advisor; Thompson, Debby, committee member; Martey, Rosa Mikeal, committee member (Colorado State University. Libraries, 2014)
Transmedia storyscapes, nonlinear narratives told across many different media platforms, have emerged as important sites of non-traditional reading and writing practices. These narratives enable a type of reading and writing that is subversive to exclusionary Western rhetorics. This study applies a Bitzerian rhetorical analysis to The Lizzie Bennet Diaries, a successful transmedia storyscape. Bitzer's definitions of exigence, audience, and constraints are challenged when applied to a transmedia text. This thesis will explore how meaningful redefinitions of key elements within Bitzer's rhetorical situation can further an understanding of transmedia. This rhetorical analysis will highlight the ways in which Rhetoric and Composition can use transmedia narratives to make space for important matters of identity and feminist forms of writing as identified by Cixous and Rich. Transmedia storyscapes are an important, though as of yet largely unconsidered, form of digital rhetorics. This thesis seeks to establish transmedia storyscapes as a viable genre of writing that successfully embodies feminist principles through the subversion of traditional writing practices.
Keywords: feminism; bitzer; narrative; rhetoric; transmedia; media